Exploration Aesthetic Values and Meaning Local Wisdom of Tongkonan Traditional Houses as Identity Toraja Tribe Society - Maulana Yuan Aldana; Sunarmi Sunarmi Sunarmi (Institut Seni Indonesia Surakarta, 2021)
The traditional Toraja house known as Tongkonan is a work of aesthetic expression and architectural image of the Toraja tribe that has the value and meaning of local wisdom in its architectural design. This study aims to further study the Tongkonan house and explore the aesthetic value and meaning of local wisdom contained in the Tongkonan traditional house as the identity of the Toraja tribal community. With qualitative research methods and data collection techniques using library studies from several sources of documents or literature related to the research topic, it can be seen if visually, the architectural design construction of the Toraja traditional house (Tongkonan) consists of the legs formed by wooden poles, the body part which contains the spaces that are lined up and the upper part is a roof made of bamboo which is divided into two and arranged overlapping each other. Each of its components is considered to have visual and ritual elements that have symbolic meaning, both in the form of the Tongkonan itself as a whole and in its complementary visual elements. From the results of this study, it can be concluded that the Tongkonan house is not only a residence for the Toraja people, but in it there are various functions and meanings that cover all aspects from belief to life which become an identity for the Toraja people themselves. both in the form of Tongkonan itself as a whole and in the complementary visual elements. From the results of this study, it can be concluded that the Tongkonan house is not only a residence for the Toraja people, but in it there are various functions and meanings that cover all aspects from belief to life which become an identity for the Toraja people themselves. both in the form of Tongkonan itself as a whole and in the complementary visual elements. From the results of this study, it can be concluded that the Tongkonan house is not only a residence for the Toraja people, but in it there are various functions and meanings that cover all aspects from belief to life which become an identity for the Toraja people themselves.